Projekt Information : Betroffene informieren Betroffene. (München : Projekt Information.)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Ickstattstrasse 28, 80469 München
Duits
Periodiek